Remembering Our Relations - Trimble, Sabina; Fortna, Peter; Athabasca Chipewyan First Nation (University of Calgary Press, 2023)
Wood Buffalo National Park is located in the heart of Dénesųłıuné homelands, where Dene people have lived from time immemorial. Central to the creation, expansion, and management of this park, Canada 's largest at nearly 45, 000 square kilometers, was the eviction of Dénesųłıuné people from their home, the forced separation of Dene families, and restriction of their Treaty rights.